2021
DOI: 10.1111/phen.12368
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition site selection and attachment ability of Propylea quatuordecimpunctata and Harmonia axyridis from the egg to the adult stage

Abstract: Surface features of plants can influence the searching efficiency and survival of predatory insects. Surfaces act as barriers preventing attachment of both phytophages and also their insect predators. In this regard, we focused on the oviposition site selection and the attachment ability of all life stages (eggs, larvae, imagines) of two common ladybird species, Propylea quatuordecimpunctata and Harmonia axyridis (Coleoptera: Coccinellidae), on artificial and natural substrates with different surface features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Another study also showed that surface roughness had little effect on the oviposition site selection of H. axyridis, although it is known to be an important factor for Propylea quatuordecimpunctata L. (Coleoptera: Coccinellidae). 31 H. axyridis females did show an ovipositional preference for the lower surface of leaves, regardless of the plant species. Coccinellids have shown different degrees of negative geotropism in egg-laying behavior, 32 including H. axyridis.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Another study also showed that surface roughness had little effect on the oviposition site selection of H. axyridis, although it is known to be an important factor for Propylea quatuordecimpunctata L. (Coleoptera: Coccinellidae). 31 H. axyridis females did show an ovipositional preference for the lower surface of leaves, regardless of the plant species. Coccinellids have shown different degrees of negative geotropism in egg-laying behavior, 32 including H. axyridis.…”
Section: Discussionmentioning
confidence: 83%
“…These results suggest that all four cover plants were suitable for H. axyridis oviposition, therefore it can be inferred that different surface features had little or no influence on the oviposition of H. axyridis . Another study also showed that surface roughness had little effect on the oviposition site selection of H. axyridis , although it is known to be an important factor for Propylea quatuordecimpunctata L. (Coleoptera: Coccinellidae) 31 . H. axyridis females did show an ovipositional preference for the lower surface of leaves, regardless of the plant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The roughness of different polishing paper with asperity sizes of 0.3, 1, 3, 9, 12, 35 and 125 μm was characterized using the white light interferometer (Salerno et al, 2017). Roughness data are reported in Salerno et al (2022).…”
Section: Preparation and Characterization Of The Tested Substratesmentioning
confidence: 99%